Household Size, Education, and Household Wealth in Indonesia: Evidence from Quantile Regression - Soseco, Thomas (Jurnal Ekonomi Indonesia, 2021)
Households need to have certain characteristics related to the ideal household size and educational attainment that allow them to accumulate wealth as a financial buffer for a period of low income. Investigation to discover those characteristics should be aimed at household classes as different classes may show various responses to the change of factors, hence, this also implies government’s interventions should be carefully aimed at different classes. In this paper, I use a quantile regression approach to measure the impact of household size and educational level on household net wealth in Indonesia. The findings show the positive and significant effect of the variable of household size in low deciles but a negative and significant effect in high deciles while the education aspect has a positive and significant effect on household net wealth with a stronger effect found in higher deciles.